Characteristics of the Cu-18.84 at.%Al-10.28 at.%Mn-1.57 at.%Ag alloy after slow cooling from high temperatures - Silva, R. A.G.; Paganotti, A.; Adorno, A. T. [UNESP]; Santos, C. M.A. [UNESP]; Carvalho, T. M. [UNESP] (Springer Nature, 2015)
The characteristics of the Cu-18.84 at.%Al-10.28 at.%Mn-1.57 at.%Ag alloy after slow cooling from high temperatures were studied using optical and scanning electron microscopies, microhardness measurements with temperature, differential scanning calorimetry, X-ray diffraction, magnetic moment changes with temperature and applied field. The results indicated the presence of a new transition associated with dissolution of the Ag-rich phase. It was also verified that the content of Al strongly interferes with the magnetization of the Cu-18.84 at.%Al-10.28 at.%Mn-1.57 at.%Ag alloy, since at lower Al concentration the relative fraction of the ferromagnetic L21-(Cu2AlMn) phase is decreased.
Keywords: Metals and alloys; Phase transformations; Thermal analysis